ANALYSIS OF DIGITAL MARKETING INFLUENCERS IN INCREASING CONSUMER TRUST IN WARDAH PRODUCTS IN MEDAN CITY THROUGH INSTAGRAM - Caya Aulia Br Ginting; Muhammad Husni Ritonga (Program Pascasarjana UIN Sumatera Utara, 2026)
The development of digital marketing has encouraged the use of Instagram influencers as a marketing communication strategy that not only expands promotional reach but also builds consumer trust in the brand. This study aims to analyze the role, obstacles, and successes of digital influencer marketing in increasing consumer trust in Wardah products in Medan City through the Instagram account @bravebeautymdn. The study used a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. The research informants included influencers and consumers who follow the account and have experience accessing Wardah promotional content. The results show that influencers act as communicators, delivering product education, user experiences, and soft-selling-based promotions that build authentic, credible, and relatable perceptions with the audience. Key obstacles include differences in consumer characteristics, the audience's tendency to compare reviews from various sources, and the emergence of negative comments. The novelty of this study lies in its focus on the local context of Medan City and the use of unofficial promotional accounts, thus enriching the study of digital marketing communication based on consumer trust in the halal cosmetics industry.